Emotion, violence, vengeance and law in the Middle Ages : essays in honour of William Ian Miller - Gilbert, Kate; White, Stephen D., 1945- (Medieval law and its practice, 2018)
"Contributions to this Festschrift for the renowned American legal and literary scholar William Ian Miller reflect the extraordinary intellectual range of the honorand, who is equally at home discussing legal history, Icelandic sagas, English literature, anger and violence, and contemporary popular culture. Professor Miller's colleagues and former students, including distinguished academic lawyers, historians, and literary scholars from the United States, Canada, and Europe break important new ground by bringing little known sources to a wider audience and by shedding new light on familiar sources through innovative modes of analysis"--Back cover